Effective separation of propylene/propane binary mixtures by ZIF-8 membranes - Pan, Yichang; Li, Tao; Lestari, Gabriella; Lai, Zhiping (Journal of membrane science, 2012)
► The first example for effective separation of C 3H 6/C 3H 8 mixtures by ZIF membranes. ► Excellent separation performance well beyond existing membranes. ► A novel process for preparation of high quality ZIF-8 membranes. ► Excellent membrane reproducibility, thermal and long-term stability. The separation of propylene/propane mixtures is one of the most important but challenging processes in the petrochemical industry. A novel zeolitic imidazole framework (ZIF-8) membrane prepared by a facile hydrothermal seeded growth method showed excellent separation performances for a wide range of propylene/propane mixtures. The membrane showed a permeability of propylene up to 200 barrers and a propylene to propane separation factor up to 50 at optimal separation conditions, well surpassing the “upper-bound trade-off” lines of existing polymer and carbon membranes. The experimental data also showed that the membranes had excellent reproducibility, long-term stability and thermal stability.